Reforms, entry and productivity: some evidence from the Indian manufacturing sector - Sumon Kumar Bhaumik; Shubhashis Gangopadhyay; Shagun Krishnan (Institute for the Study of Labor (IZA), 2006)
It is now stylized that, while the impact of ownership on firm productivity is unclear, product market competition can be expected to have a positive impact on productivity, thereby making entry (or contestability of markets) desirable. Traditional research in the context of entry has explored the strategic reactions of incumbent firms when threatened by the possibility of entry. However, following De Soto (1989), there has been increasing emphasis on regulatory and institutional factors governing entry rates, especially in the context of developing countries. Using 3-digit industry level data from India, for the 1984-97 period, we examine the phenomenon of entry in the Indian context. Our empirical results suggest that during the 1980s industry level factors largely explained variations in entry rates, but that, following the economic federalism brought about by the post-1991 reforms, variations entry rates during the 1990s were explained largely by state level institutional and legacy factors. We also find evidence to suggest that, in India, entry rates were positively associated with growth in total factor productivity.
Keywords: L11; L52; L64; L67; O14; O17; 330; entry; productivity; institutions; regulations; India; reforms; Privatwirtschaft; Produktivität; Regulierung; Markteintritt; Verarbeitendes Gewerbe; Indien